2020
DOI: 10.1039/c9ra10600f
|View full text |Cite
|
Sign up to set email alerts
|

Selection and application of aptamers with high-affinity and high-specificity against dinophysistoxin-1

Abstract: For the first time, the aptamer of dinophysistoxin-1 was successfully obtained with high affinity and specificity by SELEX, and an aptasensor with a detection range from 40 to 600 nM was developed by biolayer interferometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Therefore, aptasensors have demonstrated their useful applications for the real-time monitoring of LMW molecules such as pollutants, recreational drugs, and toxins in complex media. However, examples of BLI aptasensors for the direct detection of LMW analytes are seldom reported and are focused on marine toxins with molecular weights >411 Da …”
mentioning
confidence: 99%
“…Therefore, aptasensors have demonstrated their useful applications for the real-time monitoring of LMW molecules such as pollutants, recreational drugs, and toxins in complex media. However, examples of BLI aptasensors for the direct detection of LMW analytes are seldom reported and are focused on marine toxins with molecular weights >411 Da …”
mentioning
confidence: 99%
“…It has been reported that the affinity of several aptamers was optimized by sequence truncation [ 58 , 69 , 70 ]. Therefore, we generated some truncated forms of G48 and measured the affinity of them by BLI ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The wavelength shift is directly related to the distance between the two reflecting surfaces (i.e., it correlates with changes in the thickness of the biolayer resulting from analyte detection) [ 120 ]. This technique has been successfully used for the detection of domoic acid [ 120 ], palytoxin [ 123 ], saxitoxin [ 124 ], and dinophysistoxin-1 [ 119 ], with low LODs. In the case of palytoxin detection, the signal was amplified by HRP-labeled aptamers specific for palytoxin immobilized on the biosensor surface.…”
Section: Optical Biosensors For Detecting Aquatic Biotoxinsmentioning
confidence: 99%